Body Build and Proportions of Warsaw Youth - Grzelak, Joanna; Nieczuja-Dwojacka, Joanna; Siniarska, Anna; Samul, Ewa (Studia Ecologiae et Bioethicae, 2015)
The aim of the study was to assess changes in body build of young Warsaw pupils during the last 14 years and coming from different living conditions and lifestyle. The material comprised youth attending high school (177 individuals) aged 14-16 years. The questionnaire form included parents' education, the number of: family members, offspring, rooms, daily meals; smoking habits of parents; assessment of physical activity and stress at home, school, and high school grades. Measurements included: height and weight, upper and lower extremity length, trunk length, arm, chest, waist and hip circumferences, three subcutaneous fat folds. BMI and WHR were calculated. The living conditions were reduced by principal component analysis to three factors (family size, living conditions, environmental stress). Regression analysis showed the relation of 3 factors to body build. The current youth were characterized by greater: weight, BMI, fat tissue, trunk length and body circumferences than their coevals 14 years before. In more numerous families youth had greater trunk length. In worse living conditions they were characterized by shorter legs and more fat tissue on arm. In stress conditions youth presented greater hip circumference.